The Effect of Drinking Ionized Water on the Productive Performance, Physiological Status, and Carcass Characteristics of Broiler Chicks - Abdullah Mohamed; Mohamed Khalil; Farid Soliman; Karim El-Sabrout (Animals)
Water treatment technologies have received great attention recently, as water is the most important nutritional element, and animals consume it daily in larger quantities than those of food. The ideal water treatment affects the chemical composition and physical properties of water, having a significant positive impact on the animal’s physiology, productivity, and welfare. Studies conducted on water ionization devices for broiler chickens remain limited; therefore, this study was planned to investigate the effect of ionized drinking water on the productive performance, physiological status, and carcass characteristics of broiler chicks. A total of 900 one-day-old broiler chicks were randomly and equally assigned to three groups, each with six replicates (50 birds/replicate). The first group (C) received tap drinking water and served as a control, while the second group (T1) received ionized drinking water from an ionizing device that worked for 1 h/100 L. The third group (T2) received ionized drinking water from an ionizing device that worked for 2 h/100 L. Water analysis for each treatment was performed. Productive traits, such as weekly body weight, feed intake, and water intake, were recorded. Hematological parameters and biochemical constituents were measured according to the reference’s description. Furthermore, carcass characteristics, such as carcass weight and dressing percentage, and bacterial count of the intestine, such as Lactobacilli and Coliform counts, were determined. From the results, ionized water (T1 and T2) had a negative ORP, which is often desirable as it suggests the presence of antioxidant properties and lower total dissolved solids (TDSs), heterotrophic plate count (HPC), and algal total count (ATC) than in tap water. The treated chicks showed higher final body weights and better feed conversion rates than the control. Ionized water also improved carcass quality characteristics, such as carcass weight and dressing percentage. T1 and T2 chicks exhibited higher hemoglobin, total protein, globulin, G and M immunoglobulin, and total antioxidant capacity (TAC) levels, as well as lower malondialdehyde (MDA) and low-density lipoprotein (LDL) levels than the control. Furthermore, they had lower pathogenic bacteria counts. Therefore, it is recommended to employ the ionizing approach for broiler chicken drinking water, particularly a 2 h/100 L ionization application, for better animal productivity, health, and welfare.